Reduction of the nutritional values of diets for hens through supplementation with phytase - Lima, Matheus Ramalho de; Costa, Fernando Guilherme Perazzo; Givisiez, Patrícia Emília Naves; Silva, José Humberto Vilar da; Sakomura, Nilva Kazue [UNESP]; Lima, Denise Fontana Figueiredo (Sociedade Brasileira de Zootecnia, 2010)
Objetivou-se avaliar os efeitos da redução dos níveis nutricionais de dietas para poedeiras marrons em pico de postura sobre o desempenho das aves, a qualidade dos ovos e os parâmetros ósseos. No total foram avaliadas oito dietas, cada uma com cinco repetições de oito aves: 1. controle: formulada para suprir as exigências das aves; 2) controle + 0,03% ou 600 FTU; 3) 15% PB; 2.800 kcal de EM; 3,8% Ca e 0,28% Pd; 4) dieta 3 + 0,03% ou 600 FTU; 5) 14% PB; 2.750 kcal de EM; 3,4% Ca e 0,23% Pd; 6) dieta 5 + 0,03% ou 600 FTU; 7) 13% PB; 2.700 kcal de EM; 3,0% Ca e 0,18% Pd; e 8) dieta 7 + 0,03% ou 600 FTU. A redução dos níveis nutricionais prejudicou o desempenho das aves, principalmente a produção e massa de ovos, que melhorou com a inclusão de fitase nas dietas. Os parâmetros de qualidade dos ovos, no entanto, não se alteraram com a redução até o nível de 15% de PB; 2.800 kcal de EM/kg; 3,80% Ca e 0,280% Pd, o que não se repetiu nos níveis com menor densidade nutricional. Não houve efeito da redução dos níveis nutricionais sobre os parâmetros ósseos avaliados, exceto a resistência, que melhorou com a suplementação de fitase no nível de 600 FTU. A redução nos níveis nutricionais da dieta para 15% de PB, 2.800 kcal/kg de EM, 3,8% de Ca e 0,280% de Pd com a adição de 600 FTU não prejudica a produção nem a massa de ovos e melhora a saúde óssea das aves.

The aim of this work was to evaluate the effects of the reduction on nutritional levels of diets for semi-heavy hens during the laying peak on performance, egg quality and bone parameters. A total of eight diets were evaluated, each one with five repetitions of eight birds: 1) control: formulated to supply requirements by the birds; 2) control + 0.03% or 600 FTU; 3) 15% crude protein; 2,800 kcal ME; 3.8% Ca and 0.28% aP; 4) diet 3 + 0.03% or 600 FTU; 5) 14% crude protein; 2,750 kcal ME; 3.4% Ca and 0.23% aP; 6) diet 5 + 0.03% or 600 FTU; 7) 13% crude protein; 2,700 kcal ME; 3.0% Ca and 0.18% aP; and 8) diet 7 + 600 FTU. The reduction of the nutritional levels harmed the performance of the birds, particularly egg production and egg mass, which improved by the inclusion of phytase in the diets. However, the parameters for egg quality did not change as the level was reduced down to 15% crude protein; 2,800 kcal ME/kg; 3.80% Ca and 0.280% aP, which was not repeated in the levels with lower nutritional density. Reduction of nutritional levels did not affect the evaluated bone parameters, except for resistance, which improved as phytase was added at the level 600 FTU. Reduction on the diet nutritional levels to 15% crude protein; 2,800 kcal ME/kg; 3.80% Ca and 0.280% aP with the addition of 600 FTU of phytase does not impair egg production neither egg mass and improve the bone health of birds.
Redução do valor nutricional de dietas para poedeiras por meio da suplementação com fitase
Keywords: bone health; Eggs; Laying hens; Performance; Desempenho; Ovos; poedeiras; saúde óssea